If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 112 = -1x + 193 Reorder the terms: 112 = 193 + -1x Solving 112 = 193 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. 112 + x = 193 + -1x + x Combine like terms: -1x + x = 0 112 + x = 193 + 0 112 + x = 193 Add '-112' to each side of the equation. 112 + -112 + x = 193 + -112 Combine like terms: 112 + -112 = 0 0 + x = 193 + -112 x = 193 + -112 Combine like terms: 193 + -112 = 81 x = 81 Simplifying x = 81
| 3m-8=-3+5m | | -4-3a=-3a-4(a+2) | | 1=1+5x+2x | | X^2+3x+51=0 | | -[6x-(2x+6)]=-1-[6(2x-5)-6x] | | 2a-2=-3a+23 | | 3w-6x-y+5w+17x-6y= | | v^3-p^3=0 | | h=128t+16t^2 | | 9x^2-25x-94=0 | | x^3+3x^2+7x+21=0 | | 4(t+7)=40 | | 2+17=2m | | h=128+16t^2 | | -2y(1+9x)= | | 4x-3y+10w+4y-2w+7x= | | 2s+5+3+5s= | | A+128-34=286 | | -2(2x-5)-(x-5)=-1 | | 4(x^2+y(y+4))=12x+11 | | -[6z-(11z+9)]=9+(4z+10) | | 3-10u=-57 | | -2(t-4)=10-2r | | 7+7x=4x+3 | | 4=4-2x-4 | | 2x-15=3(5-x) | | (5x-1)(9x+3)=0 | | 6x+11=-7 | | 35mi=cm | | 4w+7y+7x+4x-14y+4w= | | 36y^2+12y+1-x^2= | | 3x+-11=10 |